Investigations on the microstructure and properties of yttria and silicon carbide reinforced aluminium composites. Issue 4 (April 2023) - Shantharaman, P.P.; Anandakrishnan, V.; Sathish, S.; Ravichandran, M.; Naveenkumar, R.; Jayasathyakawin, S.; Rajesh, S.
Abstract: Powder Metallurgy (PM) was used to synthesize SiC (0, 5, 10, 15 & 20 wt%) and 1 wt% Yttria (Y2 O3 ) reinforced aluminium (Al) metal matrix composites. The Al–SiC–Y2 O3 hybrid composites samples were prepared for density (ρ), hardness (VHN), mechanical, tribological, and microstructural studies in accordance with ASTM standards. SEM images revealed an even spreading of SiC particles throughout the Al matrix and composition was verified by the characterization techniques. The addition of SiC and Y2 O3 to their respective composites improved the VHN and 'ρ'. The compressive strength (CS) of Al–SiC–Y2 O3 composites increased while increasing the SiC. The higher compression strength (405 MPa) was obtained for the Al − 1 wt% Y2 O3 -20 wt% SiC- hybrid composites. The thermal conductivity (K) of Al–SiC–Y2 O3 samples diminishes, as the hard SiC particles are gradually added. Furthermore, it was observed that accumulative the wt% of SiC in the aluminium metal matrix (AMMC) results in a novel material with a decreased wear rate. The better properties was achieved for the samples contain 20 wt% of SiC content in Al − 1 wt% Y2 O3 matrix.